2009
DOI: 10.1519/jsc.0b013e3181b86c40
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Back Squat Training Program on Leg Power, Jump, and Sprint Performances in Junior Soccer Players

Abstract: The aim of the present study was to investigate the effects of voluntary maximal leg strength training on peak power output (Wpeak), vertical jump performance, and field performances in junior soccer players. Twenty-two male soccer players participated in this investigation and were divided into 2 groups: A resistance training group (RTG; age 17 +/- 0.3 years) and a control group (CG; age 17 +/- 0.5 years). Before and after the training sessions (twice a week for 2 months), Wpeak was determined by means of a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
202
4
18

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 241 publications
(242 citation statements)
references
References 32 publications
18
202
4
18
Order By: Relevance
“…These findings are corroborated with previous research that observed that increases in back squat strength were associated with better sprint performance after seven (Ronnestad et al, 2008) and eight weeks (Chelly et al, 2009) of resistance training in soccer players.…”
Section: Discussionsupporting
confidence: 91%
“…These findings are corroborated with previous research that observed that increases in back squat strength were associated with better sprint performance after seven (Ronnestad et al, 2008) and eight weeks (Chelly et al, 2009) of resistance training in soccer players.…”
Section: Discussionsupporting
confidence: 91%
“…1,2 It is strongly correlated with various sport performance measures such as vertical jumps and sprints, 3,4 and it is commonly prescribed by exercise professionals to enhance sport performance. 5,6 Because it is such an effective exercise, both strength and conditioning and rehabilitation professionals are continually searching for technical or external aids to help increase squatting proficiency. One possible training strategy includes the placement of resistance bands or looped elastic tubing modalities around different aspects of the lower limbs (feet/ankles/distal-lateral thighs).…”
Section: Introductionmentioning
confidence: 99%
“…The force-velocity test Force-velocity measurements for the lower limbs were performed on a standard Monark cycle ergometer (model 894 E , Monark Exercise AB, Vansbro, Sweden) as described elsewhere [14,15]. In brief, the instantaneous maximal pedaling velocity during a 7-second all-out sprint was used to calculate the maximal anaerobic power for each braking force, and the subject was judged to have reached peak power (Wpeak) if an additional load induced a decrease in power output.…”
Section: Daymentioning
confidence: 99%